A new approach to synthesize nano-yttrium boride particle through metallothermic reduction process (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
In the present study, a novel attempt is made to synthesize yttrium boride (YB4) nano-sized powders through metallothermic reduction method. The starting materials used were yttria (Y2O3), boron oxide (B2O3) as reactants and calcium (Ca) as reductant. The reaction was carried out at 9500C under argon atmosphere followed by acid washing. The product was subjected to X-ray fluorescence (XRF) which indicated its elemental constituents and purity of the prepared nanopowders. X-ray diffraction (XRD) studies revealed the formation of YB4 and YB6 phases as well as their respective crystal structures. Thermal analysis was done to calculate the weight loss and phase stability at different temperatures. It has shown complete crystallization of the yttrium boride around 8000C. Field emission scanning electron microscopy (FE-SEM) images shown the agglomerated particle morphology. Energy dispersive spectroscopy (EDS) shown the presence of Y and B elements. Transmission electron microscopy (TEM) images revealed the particle size in the order of 40 nm to 60 nm. Selected area electron diffraction (SAED) pattern are in consensus with XRD results ensuring the formation of nano-sized yttrium boride. The overall results confirmed that yttrium boride can be synthesized by the low-temperature metallothermic reduction process.